2011
DOI: 10.1515/epoly.2011.11.1.474
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive support for cell cultivation and potential grafting. Part 1: Surface modification of 2-hydroxyethyl methacrylate hydrogels for avidin immobilization

Abstract: Synthetic hydrogels are often used in biomedical applications as many of them are compatible with living tissue and moreover they can meet most criteria for artificial tissue properties. For applications in tissue engineering modification of polymer surface using some bioactive compounds (e.g. saccharides, proteins) for promoting the process of cell adhesion and proliferation is widely used. In this work, a series of modified hydrogels was prepared by three different methods: by copolymerization of 2-hydroxyet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Their preliminary cell culture results rudimentarily show the attachment of keratinocytes on surface-modified avidin-pHEMA, but no 3D system or in-depth cell response analysis. [20] In contrast to the strategies mentioned above, our system aims to provide 3D soft tissue mimic for true cell encapsulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their preliminary cell culture results rudimentarily show the attachment of keratinocytes on surface-modified avidin-pHEMA, but no 3D system or in-depth cell response analysis. [20] In contrast to the strategies mentioned above, our system aims to provide 3D soft tissue mimic for true cell encapsulation.…”
Section: Discussionmentioning
confidence: 99%
“…[18] Furthermore, this type of protein-affinity system has been exploited for many different applications in chemistry, biosciences, and tissue engineering. Indeed, modular approaches, such as the use of nanocellulose for 3D printing [19], 2-hydroxyethyl methacrylate flat substrates[20], agarose for spatial patterning [21], and porous poly-L-lactic acid scaffolds [22], have been presented and will be discussed in chapter 4.1.…”
Section: Introductionmentioning
confidence: 99%
“…The results of previous studies [ [11], [12], [13], [14], [15], [16], [17], [18]] and the study of the characteristics of roasting products showed that sulfides of non-ferrous metals obtained by sulfidation of oxides and carbonates have high hydrophobic properties, and pyrrhotite, a product of pyrite decomposition, has a significant magnetic susceptibility. All this predetermines further methods for processing sulfidation products.…”
Section: Enrichment Of Roasting Productsmentioning
confidence: 99%